Spain : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
Although not escaping the global slowdown, the Spanish economy has weathered it relatively well. The discussions focused on minimizing short-term risks and on identifying the structural reform priorities for the next government. However, household indebtedness has continued to rise rapidly, recently surpassing the EU average; the authorities viewed the related risks to growth as contained. The discussions also centered on issues of fiscal policy implementation. Although unemployment has been halved since the mid-1990s, it remains high and a number of rigidities persist.